Perceived Interpersonal Burdensomeness as a Mediator between Nightmare Distress and Suicidal Ideation in Nightmare Sufferers - Suh, Sooyeon; Schneider, Matthew; Lee, Ruda; Joiner, Thomas (Frontiers in Psychology, 2016)
Previous studies have supported the significant association between nightmares and suicidal ideation, but the underlying mechanisms are largely unknown. The purpose of the present study was to investigate perceived burdensomeness and thwarted belongingness as mediators in the relationship between nightmare distress and suicidal ideation. This sample consisted of 301 undergraduate students who endorsed experiencing nightmares (mean age 21.87 ± 2.17, 78.1% female). All participants completed questionnaires on nightmare distress (Nightmare Distress Questionnaire), unmet interpersonal needs (Interpersonal Needs Questionnaire), and suicidal ideation (Depressive Symptom Inventory - Suicidality Subscale). Analyses were performed using multiple mediation regression. Results indicated that nightmare distress was associated with perceived burdensomeness (r = .17, p < .001) and suicidal ideation (r = .24, p < .001), but was not related to thwarted belongingness (r = .10, p = .06). Multiple mediation analyses revealed that perceived burdensomeness partially mediated the relationship between nightmares and suicidal ideation, but thwarted belongingness did not. Additionally, this mediating relationship for perceived burdensomeness was moderated by gender, being significant only for females. These findings highlight the important role of interpersonal factors in the relationship between nightmares and suicidal ideation.